Alcohol consumption and household expenditure on alcohol in a rural district in Vietnam - Peter Allebeck; Kim Bao Giang; Hoang Van Minh (Taylor & Francis Group, 2013)
Introduction: Alcohol use and alcohol-related problems are on the rise in low- and middle-income countries. Expenditure on alcohol is an important problem for families and communities and needs to be assessed. Aim: This study examines level of alcohol consumption and expenditure on alcohol in a district in Vietnam. Methods: A cross-sectional survey was conducted in a rural district in northern Vietnam. Multi-stage sampling was employed to randomly select participants from 20 communities and a town in the same district. One thousand five hundred and sixty-four adults (765 males and 799 females) aged 18–60 years were interviewed. Information about alcohol use as well as expenditure on alcohol consumption four weeks prior to the interview was gathered. Non-parametric tests and log-linear regression were employed to compare expenditure on alcohol consumption across socioeconomic groups. Results: The prevalence of alcohol use one month prior to interview was 35% (66% among men and 5% among women). The median alcohol consumption among those who reported use of alcohol in the week prior to the interview was 7.9 standard drinks. Excessive drinking (more than 14 standard drinks per week for men and more than seven standard drinks per week for women) occurred among 35% of those who used alcohol. Median expenditure for alcohol consumption during one month by those who drank alcohol was USD 3.5, accounting for 4.6% of household food expenditure, 2.7% of total household expenditure, and 1.8% of household income. The differences in alcohol consumption and expenditure between sexes and between socioeconomic groups are also presented. Conclusion: Our study confirms that alcohol consumption and alcohol-related problems are common among men in Vietnam. The share of alcohol expenditure in total household expenditure is substantial, especially among poor households. This should be considered an important public health issue, which needs to be taken into account in the alcohol policy debate.